2011
DOI: 10.1007/s10140-011-0983-2
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion MRI of acute pancreatitis and comparison with normal individuals using ADC values

Abstract: The aim of this study was to retrospectively measure and compare pancreatic apparent diffusion coefficient (ADC) in patients with acute pancreatitis (AP) with aged matched controls who underwent diffusion weighted imaging (DWI). The institutional review board approved this retrospective Health Insurance Portability and Accountability Act compliant study with a waiver for informed consent. Pancreatic ADC values from 27 patients with a clinical diagnosis of AP and 38 normal age-matched controls evaluated with DW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
39
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 24 publications
4
39
0
Order By: Relevance
“…In this study, ADC values were measured under 1.62×10-3 mm 2 that were evaluated as pancreatitis. When serum leukocyte, amylase, and CRP levels turned back to normal, control imaging was again performed to compare ADC values, which also turned back to normal (19). In our study, ADC measurement was under 1.62×10-3 mm 2 in all patients.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…In this study, ADC values were measured under 1.62×10-3 mm 2 that were evaluated as pancreatitis. When serum leukocyte, amylase, and CRP levels turned back to normal, control imaging was again performed to compare ADC values, which also turned back to normal (19). In our study, ADC measurement was under 1.62×10-3 mm 2 in all patients.…”
Section: Discussionmentioning
confidence: 57%
“…However, their study has not demonstrated a measurable diffusion contrast appearance. In standard T2-weighted imaging, ADC measurement is necessary to differentiate from flare phenomenon (18,19).…”
Section: Discussionmentioning
confidence: 99%
“…Diffusion-weighted magnetic resonance imaging (DWI) has emerged as a promising technique in the early diagnosis of acute pancreatitis (AP) (1). Herein, we present a case of AP successfully demonstrated by DWI and briefly review the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Acute pancreatitis (AP) is a potentially fatal disease which has to be accurately diagnosed with a mortality rate of over 10% (Thomas et al, 2012;Shinya et al, 2008;Shinya et al, 2009;Lankisch et al, 1999). AP is mostly caused due to the obstruction extra-hepatic bile ducts and ampulla vateri by gall bladder stones and choledocholithiasis, by the tumors of bile ducts especially Klatskin tumor, by the acute and chronic inflammation of bile ducts, other etiologic conditions are: Chronic alcoholism, primary hyperparathyroidism and hypercalcemia, hypertriglyceridemia, some drugs and toxins, pregnancy, pancreatic divisum, idiopathic and etc.…”
Section: Introductionmentioning
confidence: 99%
“…(Sarles, 1963;Wang et al, 2009;Carroll et al, 2007;Wada et al, 2010). AP is a reversible inflammatory process of the pancreas, may occur as an isolated attack or may be recurrent, range in severity from mild to severe and life threatening, mild form has a low mortality rate, but patients with severe AP are more likely to develop complications and have a much higher death rate (Thomas et al, 2012;Shinya et al, 2008;Lankisch et al, 1999;Wang et al, 2009;Carroll et al, 2007;Wada et al, 2010;Triester et al, 2002;Mitchell et al, 2003;Malangoni et al, 2005). Serum amylase and lipase levels remain the most widely used diagnostic assays for acute pancreatitis, other biomarkers and inflammatory mediators such as trypsinogens are being investigated for clinical use (Smotkin et al, 2002;Frossard et al, 2001;Neoptolemos et al, 2000).…”
Section: Introductionmentioning
confidence: 99%